Forecasting the Euro: Do Forecasters Have an Asymmetric Loss Function? - Ulrich Fritsche; Christian Pierdzioch; Jan-Christoph Ruelke; Georg Stadtmann (Hamburg University, Department Socioeconomics, 2012)
Based on the approach advanced by Elliott et al. (Rev. Ec. Studies. 72, 1197-1125,2005), we analyzed whether the loss function of a sample of exchange rate forecasters is asymmetric in the forecast error. Using forecasts of the euro/dollar exchange rate, we found that the shape of the loss function varies across forecasters. Our empirical results suggest that it is important to account for the heterogeneity of exchange rate forecasts at the microeconomic level of individual forecasters when one seeks to analyze whether forecasters form exchange rate forecasts under an asymmetric loss function.
Keywords: F31; D84; 330; Exchange rate; Forecasting; Loss function